A Genetic Variation of SOD2 Does Not Determine Duration of Response to Androgen Deprivation Therapy for Prostate Cancer. Issue 14 (21st June 2016) - Xie, Wanling; Drouin, Sarah; Nakabayashi, Mari; Pomerantz, Mark; Lee, Gwo‐Shu Mary; Kantoff, Philip W.; Sharifi, Nima
Abstract : BACKGROUND: Silencing SOD2 expression upregulates androgen receptor (AR) signaling and expression of SOD2 is downregulated in CRPC, compared with untreated tumors. The decreased SOD2 activity could lead to AR gain‐of‐function and the development of castration‐resistance. METHODS: We genotyped SOD2 ‐rs4880 in a cohort of 753 prostate cancer patients receiving androgen deprivation therapy (ADT) between 1996 and 2010. The rs4880 encodes Ala16Val in SOD2 and the Val variant has been demonstrated to be functionally less efficient than the Ala variant. We assessed the impact of SOD2‐rs4880 variants on the time to progression (TTP) and overall survival (OS) on ADT using multivariable Cox regression. RESULTS: Four hundred thirty‐two out of 753 (57%) had metastases at the time of ADT initiation. Overall, median TTP on ADT was 18.4 (95%CI: 15.8, 20.9) months and median overall survival (OS) from ADT initiation was 6.3 (95%CI: 5.8, 6.8) years. In unadjusted and adjusted analyses, there was no association between SOD‐rs4880 and TTP or OS on ADT ( P > 0.05). Results were similarly negative among patients with and without metastatic disease at ADT initiation. CONCLUSIONS: Our result suggests that a functional genetic variant in SOD2 does not determine the efficacy of ADT for prostate cancer. It is possible that the drastic downregulation of SOD2 in advanced prostate cancer cells may have overridden any influence of the genetic variation of SOD2 . This study suggests the need for careful consideration about timing if the application of SOD2 mimetics for prostate cancer therapy is considered. Prostate 76:1338–1341, 2016 . © 2016 Wiley Periodicals, Inc.